(untitled) (Fiep Bulletin - online, 2016)
This work has as its main objective to evaluate the role of supervised training and the contribution of contents for teacher training student of the course Bachelor of Physical Education. Thus, it presents a theoretical framework on stage and their importance , their methodologies and then the analysis and discussion of the data from the survey conducted in the city of Patos- PB, with 30 students of Bachelor of Education physics Integrated College of Ducks , who attend between 5 and 8 period. After analyzing the data were presented in graphs, which interpretation was based on the thought of specialized authors in the area? It can be concluded positive results for teaching about the disciplines applied to the Stage Curriculum.